Reporting of study results - Beernaert, Hedwig (Henry Stewart Talks, 2012)
Definitions and basic principles, Legal requirements, Integration of reporting in the whole GLP process, Responsibilities, Planning, structure, content and deviations related to reports, Rejection of studies by the Regulatory Authorities if reports fail